New species, new records and redescriptions of Thecate hydroids (Cnidaria: Hydrozoa: Leptothecata) from Southern Australia - Watson, Jeanette E. (Zootaxa, 2011)
A collection of 13 species from southern Australia is described. The collection includes Campanulina cliftonia n. sp., Campanulina elata n. sp., Hebella albida n. sp., Antennella singulata n. sp., Ventromma bellarensis n. sp., Sertularella mytila n. sp., and Obelia spongicola n. sp. Hydranthea margarica is a new record of the genus from Australia; five other species previously recorded from Australia are redescribed in detail. The reproductive structure of Macrorhynchia whiteleggei is described for the first time allowing for a new genus species combination. Notes are given on distribution and ecology.